Progress of non-small-cell lung cancer with ROS1 rearrangement - Yang, Xin; Tang, Zhe; Li, Jing; Jiang, Jizong; Liu, Yue (Frontiers in Molecular Biosciences, 2023)
ROS1 rearrangement is found in 0.9%-2.6% of people with non-small-cell lung cancers (NSCLCs).Tyrosine kinase inhibitors (TKIs) target ROS1 and can block tumor growth and provide clinical benefits to patients. This review summarizes the current knowledge on ROS1 rearrangements in NSCLCs, including the mechanisms of ROS1 oncogenicity, epidemiology of ROS1-positive tumors, methods for detecting rearrangements, molecular characteristics, therapeutic agents, and mechanisms of drug resistance.Keywords ROS1 rearrangement, fusion gene, tyrosine kinase inhibitor, drug resistance, non-small-cell lung cancer Lung cancer remains the most fatal malignant tumor, with approximately 85% of cases being non-small-cell lung cancer (NSCLC). Of those with NSCLC, about 25% carry positive-driven gene changes that can benefit from the corresponding molecular-targeted therapy 1 . Compared with epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements, the genetic proto-oncogene tyrosine-protein kinase-1 (ROS1) is less prevalent in NSCLC, accounting for approximately 0.9% to 2.6% of cases 2,3 . The results of prospective Phase I/II clinical trials have confirmed the effectiveness of crizotinib in ROS1-positive NSCLC 4 , and in recent years, several targeted drugs, including entrectinib, ceritinib, and lorlatinib, have also shown excellent antitumor activity [5][6][7] . This article provides an overview of the progress regarding research on NSCLC with the ROS1 rearrangement.